2022
DOI: 10.1038/s41598-021-04730-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvasculature features in patients with Behcet’s disease: a systematic review and meta-analysis

Abstract: This meta-analysis aimed to analyze retinal microvasculature features in eyes with Behçet’s disease (BD) using optical coherence tomography angiography (OCTA). Electronic databases, including PubMed, Web of Science, Embase, and Cochrane Library, were comprehensively searched for published studies comparing retinal microvasculature characteristics between eyes with BD and controls. Continuous variables were calculated using the mean difference (MD) with 95% confidence interval (CI). Review Manager software (ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In a meta-analysis of cross-sectional studies comparing OCT-A findings between BD patients without ocular involvement and healthy controls, a significantly lower parafoveal capillary density and a larger foveal avascular zone (FAZ) have been reported in BD patients [35]. In another meta-analysis of OCT-A studies including BD patients with or without ocular involvement, the authors reported a high heterogeneity of results; yet pooled data showed significantly lower vessel densities in both superficial and deep parafoveal capillary plexus as well as enlarged FAZ in BD patients with ocular involvement and similar findings also in those without [36]. In a small longitudinal study, OCT-A showed significantly increased vessel density in superficial foveal capillary plexus, yet an enlarged FAZ after remission of BD uveitis [37].…”
Section: Assessment Of Disease Activity and Imaging Studies In Behçet...mentioning
confidence: 85%
See 1 more Smart Citation
“…In a meta-analysis of cross-sectional studies comparing OCT-A findings between BD patients without ocular involvement and healthy controls, a significantly lower parafoveal capillary density and a larger foveal avascular zone (FAZ) have been reported in BD patients [35]. In another meta-analysis of OCT-A studies including BD patients with or without ocular involvement, the authors reported a high heterogeneity of results; yet pooled data showed significantly lower vessel densities in both superficial and deep parafoveal capillary plexus as well as enlarged FAZ in BD patients with ocular involvement and similar findings also in those without [36]. In a small longitudinal study, OCT-A showed significantly increased vessel density in superficial foveal capillary plexus, yet an enlarged FAZ after remission of BD uveitis [37].…”
Section: Assessment Of Disease Activity and Imaging Studies In Behçet...mentioning
confidence: 85%
“…Therefore, OCT-A cannot replace FA in monitoring BD uveitis. Nevertheless, several OCT-A studies have been recently published, suggesting its use as an adjunctive imaging modality in BD uveitis [35–38]. In a meta-analysis of cross-sectional studies comparing OCT-A findings between BD patients without ocular involvement and healthy controls, a significantly lower parafoveal capillary density and a larger foveal avascular zone (FAZ) have been reported in BD patients [35].…”
Section: Assessment Of Disease Activity and Imaging Studies In Behçet...mentioning
confidence: 99%
“…One study reported the specificity of OCT-A to detect capillary dropout in superficial and deep capillary plexuses was 97% and 94% [ 35 ], but the very low sensitivity will mean OCT-A will miss a high proportion with non-perfusion on fluorescein angiography. Capillary vessel density was also explored in a recent meta-analysis in Behcet's patients regardless of retinal vasculitis [ 55 ] and showed decreased deep and superficial capillary vessel density in Behcet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in results may be due to the distinction of manifestations among different populations or the different stages of the disease. Several studies of CTDs have found that the involvement of DVD occurs earlier than that of SVD ( 34 , 40 , 41 ). In the future, longitudinal studies defining the stages of the disease may be more convincing.…”
Section: Discussionmentioning
confidence: 99%